Polemic On Church Construction in Jakarta - Ihsan Ali-Fauzi at all.; Reviewed by: Syamsul Kurniawan (Al-Albab, 2015)
Embracing religion and performing worship in accordance with one’s own preference is the right of each citizen, and is guaranteed by law. However, the ugly truth is that the Indonesian society’s tolerance is relatively low, especially in addressing the beliefs or religious differences that become an issue in the fulfillment of those rights. As a result, religious reasons often become the cause of conflicts at the grassroots level. For example, in the construction of churches, as described in the book entitled Kontroversi Gereja di Jakarta (Church Controversy in Jakarta), which was written by the research team of Paramadina Foundation, Master’s program of Peace and Conflict Resolution of Gadjah Mada University (MPRK UGM) and the Indonesian Conference on Religion and Peace (ICRP), where in the case of Jakarta, the construction of churches also often causes polemic.